The philosophical meaning of the reliefs of heaven and hell at the Pancabala temple for Buddhists at the Vipassana Graha monastery in Bandung - Damana, I Ketut; Priastana, Jo (Insan Akademika Publications, 2026)
This study aims to explore the philosophical meaning of heaven and hell in Pancabala Temple, Bandung, by explaining the issues of cosmological symbolism in the temple architecture. Data were obtained from the limitations of historical documentation and the damage of some reliefs that require a deeper philosophical interpretation. The background of the five-pointed star temple that functions as a connecting space between culture and cosmological teachings. spirituality, and morality; However, this integration element is still not coherent. The method used is a qualitative descriptive approach, combining hermeneutic analysis with symbolic interpretation to reveal the philosophical messages embedded in the temple reliefs. The results of primary data were obtained from the observation that heaven and hell function as a moral framework that guides human behavior. Secondary data were obtained from the drafts of illiterate humans, which sparked debate about the reality of life after death, and can be interpreted as a state of consciousness that arises from human actions. The results of the philosophical analysis concluded that the construction of the analyzed temple is a Buddhist legacy that contributes to a new understanding of the values of moral and cosmological education inherited from ancestors and highlights its relevance regarding old cultural education adopted in modern times